PENDAMPINGAN BELAJAR KELOMPOK BERBANTUAN FUN PUZZLE - Firda Alfiana Patricia; Kenys Fadhilah Zamzam (JPM PAMBUDI, 2022)
The learning process carried out at each individual's home experienced many obstacles during its implementation, including students easily bored, students' interest in learning decreased, and the learning process carried out was less focused so that the learning process was less effective. The learning process individually experiences obstacles because parents pay less attention to their children's learning process for reasons of being busy working, besides that it is also caused by a lack of knowledge. One solution to overcome this problem is through learning assistance activities which are part of the form of community service. Learning assistance through tutoring activities can improve achievement as well as learning motivation. The implementation of learning assistance with the group work method consists of five stages including: preparation, assessment, planning, intervention, and termination. The existence of this learning assistance activity helps students' ways of thinking become more open so that apart from influencing academics, they also learn how to socialize. This is evidenced by changes in attitude before the activity is carried out and after the activity is carried out.